The Relationship Between the Audit Board of the Republic of Indonesia's (BPK) Opinion With Regional Government Financial Report and Corruption - Idrus, Yudi Avalon; Achsani, Noer Azam; Hardiyanto, Arief Tri (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2018)
BPK audit report on a government financial report contains an opinion that is a professional statement of the auditor regarding the fairness of financial information presented in the financial statement. In forming an opinion, a BPK auditor uses four criteria: the application of the Government Accounting Standard, adequate disclosures, compliance with laws and regulations, and effectiveness of internal control systems. The unqualified opinion is issued to a financial report with no material statements and/or fraud. However, it is widely reported that many irregularities still occur across government entities and cost the state's resources (finance). This study aims to analyze corruption committed by heads of local governments and its influence on BPK opinion and build a model which shows the relationship between them. This study uses a model called ordinal logistic regression and finds a correlation between BPK opinion and corruption committed by heads of local governments. The best ordinal logistic regression model shows that BPK opinion is dominantly influenced by the compliance of government financial reports with Government Accounting Standard, compliance with laws and regulations, and effectiveness of internal control systems.